On infinite-rank singular perturbations of the Schrödinger operator - Kuzhel', S. A.; Vavrykovych, L. (Ukrains’kyi Matematychnyi Zhurnal, 2008)
Schrodinger operators with infinite-rank singular potentials ^∞_i,j=1b_i,j(ψ_j,·)ψ_i are studied under the condition that singular elements ψ_j are ξ_j(t)-invariant with respect to scaling transformations in R^3.